Consumer acceptance of RISDA rural industrial products . An analysis of RISDA's marketing strategy / Zamira Maarof - Maarof, Zamira (Faculty of Business and Management, 2008)
The purpose of this research is to measure the consumer acceptance of RISDA rural industrial product, an analysis of RISDA's marketing strategy. The dependent variable is consumer acceptance and independents variables are product development, promotion strategies and market development. The research is conducted at Melaka area. In completing this research about 100 questionnaires has been distributed to the respondents. The respondents are included all public who have and have not consumed the rural industry products. In order to get the result from this research, the researcher has used SPSS program to analyze data from the information gathered. To analyze the data, the researcher has been used Reliability Analysis, Frequency Distribution and Descriptive Statistic by using the SPSS program. From the findings the research indicates that most of the respondents agree the rural industry products are acceptable but RISDA's marketing strategy has to improve because it is not effective to attract consumer acceptance. In term of product development, RISDA has to impress in the consumers through effective branding, labeling and packaging of the products, so that they are more informative and attractive. Beside that, the promotion strategy that RISDA has been implementing before, like price discounting and exhibition of rural industry products have to be more commercial-based so as to create respondents awareness of the products. Regarding to the market development, it is shows that the number of outlets that sell rural industry products are still limited in Melaka area. However, based on the research, the distributors are interested to distribute the products and need co-operation between producer and supplier to produce the products in bulk so as to fulfill the increasing demand.